THE ROLE OF LOGARITHMIC-NORMAL DISTRIBUTION MODELS IN ASSESSING THE RELIABILITY OF BEARING LIFE - Khalilov Murodiljon Durbek son; Komiljonov Babur Comiljon son (Bright Mind Publishing, 2025)
In the article log-normal distribution model in engineering, especially bearings work the deadline in the evaluation importance seeing the model is main formulas, statistics indicators and practical results statement is being done.
Keywords: Log-normal distribution, bearing, reliability, mathematical model, statistical analysis.